A Scientometric Study of the Brand Building Process in Organizations - Dr. Amir Saeed; Asma Rehman; Dr. Awais Alam (International Journal of Experiential Learning & Case Studies, 2024)
Brand building has been suggested as an important process in the success of any business. In order to find out brand building framework for SMEs literature review was conducted, the problem identified from literature is that there is a lack of structured brand building framework for SMEs as compare to big Corporations and MNCs. Brand building conceptual model emerging from this review can allow SMEs to establish distinguished brand identity that help them to survive and enhances business performance, it can change how people perceive brand, it can drive new business, and increase brand value. Furthermore, new moderating variable employee-brand knowledge has been incorporated into the proposed framework. This research also adds to the already existing body of literature and also provide basis for future research studies.